Clinicopathological and Fecal Proteome Evaluations in 16 Dogs Presenting Chronic Diarrhea Associated with Lymphangiectasia - Giacomo Rossi; Alessandra Gavazza; Silvia Vincenzetti; Sara Mangiaterra; Livio Galosi; Andrea Marchegiani; Graziano Pengo; Gianni Sagratini; Massimo Ricciutelli; Matteo Cerquetella (Veterinary Sciences, 2021)
Canine intestinal lymphangiectasia (IL) is a condition characterized by variably severe gastrointestinal signs, frequently associated with laboratory abnormalities; the research for markers allowing a better understanding of the severity degree and/or obtaining an early diagnosis and/or monitoring is continuously progressing. In the present study, we investigated possible new diagnostic/follow-up markers in IL dogs, namely, serum C-reactive protein, serum bacterial lipopolysaccharide, serum cleaved cytokeratin 18, serum citrulline, and zonulin (in both serum and feces). A fecal proteomic study looking for possible confirmation and/or new marker candidates was also performed. All markers in both substrates, with the exception of serum citrulline, significantly differed between diseased and control dogs. Fecal proteomics allowed the retrieval of three proteins in IL dogs (Fc fragment of IgG-binding protein; transthyretin; proproteinase E) that were not previously found in clinically healthy subjects. Although further studies are needed, C-reactive protein, bacterial lipopolysaccharide, cleaved cytokeratin 18, and zonulin (in both serum and feces) resulted as promising markers for canine IL; similarly, fecal proteomics represents a road worthy of being pursued in the search for candidate biomarkers.